Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/s10681-006-9088-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Resistance to Tobacco Cutworm (Spodoptera litura F.) and their Implications to Screening for Resistance in Groundnut

Abstract: The Tobacco cut worm (Spodoptera litura Fab.), a polyphagous defoliating insect is a major pest on groundnut in Asia. Screening germplasm for resistance to Spodoptera litura in the field under high infestation revealed significant genotypic variation. Low damage was observed on Mutant (28-2), NC Ac 343, ICGV 86031, R 9227 and TAG 24. In the laboratory rearing of insect, the resistant genotypes, NC Ac 343, Mutant 28-2 and R 9227 affected larval growth and survival, pupal development, adult emergence and fecundi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Identification of potential resistant sources for Spodoptera litura is a pre-requisite for developing resistant cultivars. Earlier, ICGV 91180, NC Ac 343, M 28-2 and M 45 (Prasad and Gowda 2006;Naidu et al 2016) were identified as resistant to Spodoptera litura with less leaf damage. Identification of diverse sources of resistance would help in avoiding break down of resistance.…”
Section: Introductionmentioning
confidence: 98%
“…Identification of potential resistant sources for Spodoptera litura is a pre-requisite for developing resistant cultivars. Earlier, ICGV 91180, NC Ac 343, M 28-2 and M 45 (Prasad and Gowda 2006;Naidu et al 2016) were identified as resistant to Spodoptera litura with less leaf damage. Identification of diverse sources of resistance would help in avoiding break down of resistance.…”
Section: Introductionmentioning
confidence: 98%
“…Spodoptera litura has developed resistance to a number of synthetic insecticides (Kranthi et al 2002). ICGV 86699 and NCAC 343 differ in the maturity period (Prasad and Gowda 2006) and levels of resistance to different insects .…”
Section: Introductionmentioning
confidence: 99%
“…The average yield at around 1,000 kg/ha, is lower than other major peanut growing countries due to losses caused by biotic stresses like diseases and insect pests (Desai et al 1999;Ghewande et al 2002). Although there are some commercial cultivars which show moderate level of resistance but undesirable agronomic features like low shelling, undesirable pod and kernel traits make them less popular (Patil et al 1995;Prasad and Gowda 2006). Some of the wild relatives in Arachis genera carry genes for resistance against certain diseases and pests (Stalker and Moss 1987).…”
Section: Introductionmentioning
confidence: 99%